2018
DOI: 10.5812/semj.74125
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Adherence in Patients with Hypertension: A Cross Sectional Study from Southeast of Iran

Abstract: Background: Poor adherence to antihypertensive treatment has been a global challenge. It is necessary for health care providers to identify the factors affecting treatment adherence. Objectives: The present study aimed to investigate the adherence to treatment and its related factors in patients with hypertension. Methods: A cross sectional study carried out from September 2017 to March 2018 on 600 patients with hypertension who were covered by urban community health centers in Kerman, Iran. The Persian versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…For instance, a few studies conducted in Palestine on patients with DM using the MMAS questionnaire have shown an adherence rate for DM medications between 56% and 73% [31]. A review of patients with DM in the Middle East and North Africa conducted in 2017 concluded that the average medication low adherence in this region was of 38%, compared to the 30% reported in our study [24,32,33]. The countries of the Gulf, high-income countries, appeared to be more prone to low adherence with a reported average of 40% [18,34].…”
Section: Discussioncontrasting
confidence: 57%
“…For instance, a few studies conducted in Palestine on patients with DM using the MMAS questionnaire have shown an adherence rate for DM medications between 56% and 73% [31]. A review of patients with DM in the Middle East and North Africa conducted in 2017 concluded that the average medication low adherence in this region was of 38%, compared to the 30% reported in our study [24,32,33]. The countries of the Gulf, high-income countries, appeared to be more prone to low adherence with a reported average of 40% [18,34].…”
Section: Discussioncontrasting
confidence: 57%
“…Most of the studies were published after 2015, and only 5 studies were published between 2004 and 2014. Six randomized controlled trial studies [17,21–25], one quasi-experimental study [26], and 24 cross-sectional studies [16,18–20,27–44] were identified for conducting the present study. The total number of participants in the study was 8409.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, two studies used census [20,40]. Finally, 11 studies used cluster sampling [18,28,30,31,33,34,37,38,42,46].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations